AKIBAT HUKUM TERHADAP WALI DALAM MEWAKILI ANAK DI BAWAH UMUR DIHADAPAN NOTARIS - EKA RAHMAT GUNAWAN; Shinta Andriyani (Private Law, 2023)
This study aims to analyze the legal consequences and responsibilities of guardians in representing minors before a Notary based on Decision Number 18/Pdt.P/2023/PA.TPI. The approach used is statutory, conceptual approach. The legal sources used are primary and secondary legal materials. Techniques / ways of obtaining legal materials are carried out by literature study. The analysis used in this research is qualitative analysis. Based on the results of the research, the legal consequences and responsibilities of guardians in representing minors based on decision Number 18/Pdt.P/2023/PA.TPI, namely the emergence of rights and obligations, the authority to represent minors in carrying out legal acts determined by law and guardians are responsible for ensuring the welfare and future of the children they care for.